In‐Depth Extracorporeal Cardiopulmonary Resuscitation in Adult Out‐of‐Hospital Cardiac Arrest. Issue 10 (18th May 2020) - Dennis, Mark; Lal, Sean; Forrest, Paul; Nichol, Alistair; Lamhaut, Lionel; Totaro, Richard J.; Burns, Brian; Sandroni, Claudio
Abstract: The use of extracorporeal cardiopulmonary resuscitation (E‐CPR) for the treatment of patients with out‐of‐hospital cardiac arrest who do not respond to conventional cardiopulmonary resuscitation CPR) has increased significantly in the past 10 years, in response to case reports and observational studies reporting encouraging results. However, no randomized controlled trials comparing E‐CPR with conventional CPR have been published to date. The evidence from systematic reviews of the available observational studies is conflicting. The inclusion criteria for published E‐CPR studies are variable, but most commonly include witnessed arrest, immediate bystander CPR, an initial shockable rhythm, and an estimated time from CPR start to establishment of E‐CPR (low‐flow time) of <60 minutes. A shorter low‐flow time has been consistently associated with improved survival. In an effort to reduce low‐flow times, commencement of E‐CPR in the prehospital setting has been reported and is currently under investigation. The provision of an E‐CPR service, whether hospital based or prehospital, carries considerable cost and technical challenges. Despite increased adoption, many questions remain as to which patients will derive the most benefit from E‐CPR, when and where to implement E‐CPR, optimal post‐arrest E‐CPR care, and whether this complex invasive intervention is cost‐effective. Results of ongoing trials are awaited to determine whether E‐CPR improves survival when compared with conventional CPR.